The will of bishop Alonso de Burgos : religious belief, memory and ecclesiastical prominence in Castilian Kingdom at the end of XV century (Estudios de Historia de España, 2021)
In the present article we analyze and publish the will given in 1499 by Alonso de Burgos, then bishop in Palencia, a personality connected to the Reyes Católicos and founder of Saint Gregory College in Valladolid. The interpretation of his will displays the ecclesiastical and social prominence of this bishop, his huge economic power, his support to the monastic reformation, his effort to achieve the absolution of purgatory´s punishments paying the celebration of thousands of mass and giving money for poor persons and liberation of christian captives, and, finally, his effort to perpetuate his own memory.
Keywords: Alonso de Burgos; Saint Gregory College in Valladolid; Wills; Memory; Religious belief